Catalytic and Stereoselective ortho‐Lithiation of a Ferrocene Derivative1. Issue 37 (23rd July 2013) - Steffen, Patricia; Unkelbach, Christian; Christmann, Mathias; Hiller, Wolf; Strohmann, Carsten
<x xml:space="preserve">Abstract</x> N , N‐Dimethylferrocenylmethylamine can be lithiated stereoselectively by iPrLi in pentane/Et2O using catalytic amounts of the chiral auxiliary (R, R)‐TMCDA. In homogenous reactions, high e.r. values were obtained upon crystallization of the lithiated species. The catalytic activity of TMCDA is made possible by its release from the stereomerically pure lithioferrocene as it dimerizes to a homochiral dimeric etherate.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>